TEOLOGI KEHENDAK BEBAS: LANDASAN TEOLOGI STRATEGI PEMURIDAN TERHADAP PERILAKU SEKSUAL - Kadarisman, Terry; Perangin Angin, Yakub Hendrawan; Lie Lie, Tju (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2023)
This study aims to formulate theology of free will as the theological foundation of discipleship strategy of sexual behavior based on 1 Corinthians 6:12-20. The purpose of this paper are based on the reality that there is no discipleship strategy of sexual behavior that are designed specifically to urge youth to control their sexual behavior. The method that are used in this paper is qualitative research method with literature study approach. The paper found that 1 Corinthians 6:12-20 shows discipleship strategy that are done by Paul to the congregation of Corinthians with emphasized to the theology of free will as the solution to control sexual behavior, so that can be the foundation of discipleship strategy of sexual behavior subject matters. Paul studied about free will in his letter by associate it with other theological themes, to wit anthropology, eschatology, christology, ecclesiology, flesh oneness, hamartology, pneumatology, proper, and soteriology. Comprehensive study that Paul has done shows that free will in fact take roles in determines way of life, especially related to someone’s sexual behavior. This paper can conclude that the theology of freewill can be the theological foundation of discipleship strategy of sexual behavior, especially in arranging discipleship of sexual behavior subject matters.